2019
DOI: 10.1111/jfpe.13053
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing precooling of large beef carcasses using a comprehensive computational fluid dynamics model

Abstract: Precooling has been questioned as a suitable step in the process of beef carcass cooling. Model‐based optimization was performed to identify optimum operating conditions for different heavy‐muscled beef carcass cooling practices in slaughterhouses with both precooling and cooling stages. The study was conducted using a validated computational fluid dynamics model of the beef carcass cooling process. The precooling practice was optimized based on a weighted impact function taking into account energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…[15]. WHC can be measured as drip loss dependent on the body temperature of the carcass and the velocity, humidity, and temperature of the air in the chilling room [16]. Many factors influence WHC, which include physiological (pH, breed, sex, age, muscle type, area of muscle), rearing conditions (feeding, administration, pre slaughter), slaughter conditions (killing method, handling, packing, storage, freezing, thawing, and aging) [17].…”
Section: Water Holding Capacitymentioning
confidence: 99%
“…[15]. WHC can be measured as drip loss dependent on the body temperature of the carcass and the velocity, humidity, and temperature of the air in the chilling room [16]. Many factors influence WHC, which include physiological (pH, breed, sex, age, muscle type, area of muscle), rearing conditions (feeding, administration, pre slaughter), slaughter conditions (killing method, handling, packing, storage, freezing, thawing, and aging) [17].…”
Section: Water Holding Capacitymentioning
confidence: 99%
“…The results revealed the advantage of utilizing a precooling unit that works with an optimum choice of velocity, cooling air temperature, and precooling time. They concluded that using low air velocity at −30°C is more beneficial than using a high airflow fan that consumes high energy value (Delele et al, 2019).…”
Section: Introductionmentioning
confidence: 99%